Silicon and Plants: Current Knowledge and Technological Perspectives - Luyckx, Marie; Hausman, Jean-Francois; Lutts, Stanley; Guerriero, Gea (Frontiers in Plant Science, 2017)
Elemental silicon (Si), after oxygen, is the second most abundant element in the earth’s crust, which is mainly composed of silicates. Si is not considered essential for plant growth and development, however increasing evidence in the literature shows that this metalloid is beneficial to plants, especially under stress conditions. Indeed Si alleviates the toxic effects caused by abiotic stresses, e.g. salt stress, drought, heavy metals, to name a few. Biogenic silica is also a deterrent against herbivores. Additionally, Si ameliorates the vigour of plants and improves their resistance to exogenous stresses. The protective role of Si was initially attributed to a physical barrier fortifying the cell wall (e.g. against fungal hyphae penetration), however several studies have shown that the action of this element on plants is far more complex, as it involves a cross-talk with the cell interior and an effect on plant metabolism. In this study the beneficial role of Si on plants will be discussed, by reviewing the available data in the literature. Emphasis will be given to the protective role of Si during (a)biotic stresses and in this context both priming and the effects of Si on endogenous phytohormones will be discussed. A whole section will be devoted to the use of silica (SiO2) nanoparticles, in the light of the interest that nanotechnology has for agriculture. The paper also discusses the potential technological aspects linked to the use of Si in agriculture and to modify/improve the physical parameters of plant fibers. The study indeed provides perspectives on